ANALISIS KESULITAN KONSEPTUAL SISWA PADA MATERI LIMIT FUNGSI DALAM PEMBELAJARAN MATEMATIKA - Eka Putri, Aulia; Mula Defi, Aprilia; Sulistiyani, Fani; Puji Astuti, Yunisyia (STKIP Subang, 2026)
This study aims to analyze students’ conceptual difficulties with the topic of limits of functions in mathematics education. This study employs a literature review method using the Systematic Literature Review (SLR) approach. The research data consist of scientific articles obtained from various academic databases through purposive sampling based on specific criteria, namely topic relevance, publication years from 2020 to 2025, and having undergone a peer-review process. Data analysis was conducted through the stages of identification, selection, classification, and thematic synthesis of the research findings. The results indicate that students’ difficulties with the topic of limits of functions can be classified into three main aspects: conceptual, procedural, and technical. Difficulties in the conceptual aspect were the most frequently observed, particularly in understanding the definition of a limit, distinguishing between left-hand and right-hand limits, and interpreting the behavior of functions. Difficulties in the procedural and technical aspects generally arise as a result of students’ weak conceptual understanding. Additionally, students’ difficulties are also influenced by factors such as mastery of prerequisite material, misconceptions, and a learning process that does not fully support deep conceptual understanding. These findings indicate that strengthening conceptual understanding is crucial in teaching limits of functions through the use of various representations and learning strategies that are more student-centered.